Pemanfaatan Metode Irigasi tetes Sederhana Untuk Budidaya Tanaman Hortikultura Di Desa Ungga, Kecamatan Praya Barat Daya, Kabupaten Lombok Tengah: Pemanfaatan Metode Irigasi tetes Sederhana Untuk Budidaya Tanaman Hortikultura Di Desa Ungga, Kecamatan Praya Barat Daya, Kabupaten Lombok Tengah - Fifi Lofiana Tenggara; Baiq Handayani Rinuastuti; Zulya Handayani; Baiq Parasmita Tri Anjani (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Drought is a problem that is often experienced by the community, especially the people in Ungga village. The problem of drought is the cause of the lack of use of home yard land for planting food crops such as vegetables. In Ungga village there is quite a lot of vacant land that is not used. One of the efforts that can be used to save water use in crop irrigation is by applying a drip irrigation system. This drip irrigation system has advantages such as saving water usage and saving time because watering is done automatically. Making a simple drip irrigation device using materials that are easy to obtain used plastic bottles and waste infusion bottles. Not only making drip irrigation equipment, but also socializing the use of simple drip irrigation equipment to the people of Ungga Village.